Investigation of paeonol in dermatological diseases: an animal study review - Ju, Jingyi; Song, Tianyu; Shi, Jia; Li, Jialun (Frontiers in Pharmacology, 2024)
Cortex Moutan is the root bark of the buttercup plant Paeonia suffruticosa Andr, of Ranunculaceae family. It has been utilized in Chinese medicine for thousands of years to treat a multitude of diseases, and traditional Chinese documents allege that it has heat-clearing, antipyretic, anti-inflammatory and detoxicating properties. Paeonol is a bioactive substance extracted from Cortex Moutan, which is considered to be one of its most effective metabolites. Recent studies have illustrated that paeonol treatment can alleviate skin damage, relieves the inflammatory response in patients with numerous dermatological conditions, and inhibits anomalous proliferation of skin tissue. Accordingly, paeonol may serve as a potential therapeutic agent for a variety of skin conditions. This review summarizes the physicochemical properties and pharmacokinetics (PK) characteristics of paeonol, and mechanisms of operation in diverse skin diseases, including dermatitis, psoriasis, pruritus, photoaging, and hyperpigmentation, hyperplasticscar, and much of the evidence is based on animal experiments. Furthermore, it explores the prospects of enhancing paeonol's efficacy through extraction, synthesis, and formulation innovations, as well as strategies to overcome its limitations in dermatological therapy. This review aims to provide a more reliable theoretical basis for the clinical application of paeonol.